Development of STEM-Based LKPD with Guided Inquiry Design to Improve Student’s Science Process Skills - Sella Afrianti; Nanda Novita; Fajrul Wahdi Ginting; Syafrizal Syafrizal; Syarifah Rita Zahara (Universitas Muhammadiyah Purworejo, 2022)
This study aims to develop a STEM-based Student Worksheet (LKPD) through Guided Inquiry to Improve Students' Science Process Skills. This research and development method refers to the Borg & Gall model up to the 8th stage, namely a trial use that has been adapted to research needs, namely developing LKPD and seeing an increase in students’ science process skills after using LKPD in learning activities, with research subjects in class XI IPA 5 and XI. IPA 3, each totaling 24 students. The results obtained are: 1) the validation of the LKPD that has been developed is